Secure e-transactions protocol using intelligent mobile agents with fair privacy - Han, Song; Chang, Elizabeth; Dillon, Tharam S. (Springer-Verlag, 2006)
Electronic commerce has pushed and benefited from the development of intelligent mobile agents technology. One of the reasons is electronic commerce needs remote searching and negotiating between one customer and a number of E-shops. This chapter presents a new secure electronic commerce protocol. We provide the security mechanisms through using a new proxy signature scheme implied in the protocol. The digital age has enabled widespread access to and collection of data. While there are several advantages to ubiquitous access to data, there is also the potential for breaching the privacy of individuals. Therefore, preserving privacy is maintained for both the customer and the e-shops in the proposed e-transactions. In addition, fair privacy is one of the characteristics of the new protocol. The proposed e-transactions use intelligent mobile agents to help customers make buying decisions, as well as providing post-purchase service for customers, and providing post-purchase auditing for e-shops. Therefore, it will improve the successful e-commerce to satisfy customers and increase sales of e-shops.